Production of bio-dimethyl ether from oil palm residue via integrated gasification and direct DME synthesis process - Im-Orb, Karittha; Arpornwichanop, Amornchai (My University, 2023)
The production of bio-dimethyl ether via an integration of biomass gasification and direct DME synthesis (IBG-DME) was studied. The oil palm residue was a considered feedstock. The parametric analysis was done to examine the impact of gasifying temperature on the product composition, energy demand of each unit and overall process using the developed Aspen plus model. The high gasifying temperature offered high production rate of valuable products (bio-DME and bio-methanol), and low CO2 emission. The IBG-DME process could operate at thermal self-sufficient condition when gasifying temperature was maintained at 882 °C. The maximum yield of bio-DME of 0.3472 kg.h-1 could be achieved at gasifying temperature of 950 °C. At this condition, the CO2 emission, overall energy consumption and energy efficiency were 0.7457 kg.h-1, 0.00776 kW and 59.76 %, respectively.